YODISASI GARAM RAKYAT DENGAN SISTEM SCREW INJECTION - Hartati, Retno; Supriyo, Edy; Zainuri, Muhammad (Vocational School Diponegoro University, 2014)
Retno Hartati, Edy Supriyo, Muhammad Zainuri, in this paper explain that many salt industry is currently undergoing a inefficiencies process in the production system. Declining quality of salt from the salt ponds and lack of homogeneity in the iodine content of salt briquettes and much KIO3 wasted. So it is necessary to increase the iodine levels in salt. This activity aims to design, create and test a iodized salt machine with a capacity of 1-2 tons per hour and perform quality control on products. Community service activities have been successfully implemented by creating iodized salt machine. The process is done by means of iodized salt machine in the salt product becomes higher and meet ISO standards, in which prior to iodized salt machine the content of KIO3 is 0 ppm and become 50 ppm after using KIO3. Keywords : yodization, salt,screw, injection